RASIO-RASIO KESEHATAN LPD YANG BERADA DI DAERAH PARIWISATA DAN NON PARIWISATA PADA MASA PANDEMI COVID-19 - Ersania, Gusti Ayu Raisa (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022, 2022)
The importance of the soundness of banks in determining policies to maintain company operations in the face of competition between the same type of business, so this research was carried out using the CAMEL method on LPDs during the Covid-19 pandemic. The sample used in this study were 20 LPDs in Badung Regency. The analytical technique used to identify and identify the health ratios of LPDs in the area and tourism during the COVID-19 pandemic in this study was the CAMEL method and the t-test difference. The results of this study indicate that the CAR, KAP, Management, ROA and Liquidity of LPDs located in tourism areas and non-tourism areas are included in the healthy category during the COVID-19 pandemic, while Assets Quality, Earning and BOPO LPDs located in tourism and non-tourism areas. non-tourism is included in the unhealthy category.